2021
DOI: 10.7554/elife.66898
|View full text |Cite
|
Sign up to set email alerts
|

Electrical synaptic transmission requires a postsynaptic scaffolding protein

Abstract: Electrical synaptic transmission relies on neuronal gap junctions containing channels constructed by Connexins. While at chemical synapses neurotransmitter-gated ion channels are critically supported by scaffolding proteins, it is unknown if channels at electrical synapses require similar scaffold support. Here, we investigated the functional relationship between neuronal Connexins and Zonula Occludens 1 (ZO1), an intracellular scaffolding protein localized to electrical synapses. Using model electrical synaps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 99 publications
1
57
0
Order By: Relevance
“…Connexins, yet it itself is necessary for these proteins to robustly localize to the developing synapse. Furthermore, we have identified a biochemical connection between Neurobeachin and ZO1b, and previous work found that ZO1b in turn binds Cx34.1 (Lasseigne et al, 2021). Thus, our emerging model is that Neurobeachin sits at the top of an electrical synapse hierarchy, directing ZO1b to the synapse, which in turn brings in the Connexin to build the neuronal gap junction.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Connexins, yet it itself is necessary for these proteins to robustly localize to the developing synapse. Furthermore, we have identified a biochemical connection between Neurobeachin and ZO1b, and previous work found that ZO1b in turn binds Cx34.1 (Lasseigne et al, 2021). Thus, our emerging model is that Neurobeachin sits at the top of an electrical synapse hierarchy, directing ZO1b to the synapse, which in turn brings in the Connexin to build the neuronal gap junction.…”
Section: Discussionmentioning
confidence: 58%
“…Electrical synapse structure and function is built hierarchically wherein ZO1b is required for Connexin localization, but ZO1b largely localizes independently of the Connexins (Lasseigne et al, 2021). We therefore sought to determine if localization of Neurobeachin to the electrical synapse was dependent on ZO1b or Connexins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our FIB-SEM material, and appropriately fixed SBF-SEM material, the pentalaminar structure of gap junctions cannot be resolved but an area of increased membrane density and chromophilic staining is present where the membranes of a cone telodendron and a rod spherule merge. The identity of the chromophilic material is unknown but presumably it represents the aggregation of connexons and auxiliary proteins at gap junction sites (Lasseigne et al, 2021;Nagy et al, 2018). For rod spherules, this coincides with the location of Cx36 labeling, close to the mouth of the synaptic opening, and so there is a high probability that these sites represent gap junctions.…”
Section: Identification Of Gap Junctionsmentioning
confidence: 94%
“…Moreover, recent evidence suggests that proper function and plasticity of gap junctions depend on the interaction with multimolecular complexes composed of proteins involved in cell adhesion, scaffolding, trafficking, and protein kinases [ 8 , 9 , 10 ]. For instance, the scaffold protein zonula-occludens-1 has been shown to interact with the C-terminal tail of Cx34.1, homologous to mammalian Cx36 in fish, and its presence is essential for the structure and function of electrical synaptic transmission [ 11 , 12 ]. The cytoskeleton protein tubulin has also been shown to interact with Cx36 at the C-terminal domain, suggesting the existence of a tubulin-dependent transport involved in the regulation of gap junction resistance and size [ 13 ].…”
Section: Gap Junctions As the Structural Substrate Of Electrical Synapsesmentioning
confidence: 99%